Sex differences in dynamic knee stability in high intensity functional training athletes. - Kurtz, Brady Kent (Kansas State University, 2020)
INTRODUCTION. Acute anterior cruciate ligament (ACL) injury is the single greatest concern in modern orthopedic sports medicine. While sex is a known predictor for knee injury among sporting populations, relative risks for knee injuries among men and women in high intensity functional training (HIFT), an activity that blends sport and fitness together, are unknown. Further investigation into the fatigue-related compensation mechanisms and dynamic knee stability of HIFT-trained athletes is necessary to understanding the comparative risk of participation in these exercise modalities. METHODS. Participants completed a single-group 2-visit assessment protocol consisting of a familiarization session in which anthropometric data were collected, as well as a testing session. During the testing session, participants completed a three-round HIFT workout, as well as a biomechanical performance analysis utilizing the single-leg squat and drop vertical jump before and after each round of the workout. RESULTS. No significant differences existed in mean round times between sexes (F=.53, p=.48, η²=.03), as well no significant main effect for time (F=3.60, p=.07, η²=.17) or interactions between sex and time were detected (F=.01, p=.95, η²=0). There was a significant main effect of time on heart rate (F=213.31, p<.001, η²=.92) and rate of perceived exertion (F=22.75, p<.001, η²=.56), but no interaction between sex or sex*time existed for either variable. No significant multivariate effects for time or interaction between sex*time were present for stance time or jump height. There was a significant multivariate main effect for sex on baseline drop vertical jump and right single-leg squat kinematics and kinetics, but not for the left single-leg squat (F=1.29, p=.26, η²=.26). These sex differences during the drop jump and right single-leg squat existed across all time points, but no significant multivariate main effects for time (drop vertical jump: right leg: F=1.11, p=.31, η²=.06; left leg: F=1.7 p<.01, η²=.09; Right single-leg squat: F=.78, p=.83, η²=.05) or sex*time (drop vertical jump: right leg: F=.76, p=.85, η²=.04; left leg: F=1.08, p=.34, η²=.06; Right single-leg squat: F=1.08, p=.35, η²=.04) were found between groups. No multivariate main effects for time (F=.70, p=.91, η²=.04) or interaction between sex and time (F=0.60, p=.97, η²=.03) existed during the left single-leg squat. DISCUSSION. While participants perceived themselves be working harder as the workout progressed, results did not suggest fatigue was present. No differences were detected at baseline for the left single-leg squat. Conversely, right single-leg squat baseline data suggested that women have less dynamic control of their dominant limb than men. While sex differences existed across all timepoints for both movements, time and sex*time were not predictors for deterioration in knee mechanics. CONCLUSION. Further, while sex differences existed in movement mechanics, they did not deteriorate throughout the workout, suggesting that HIFT may not induce levels of fatigue significant enough to compromise movement mechanics. This study also suggests that HIFT trained women’s movement mechanics appeared superior to what has been previously reported in the literature.
Keywords: HIFT; high intensity functional training; CrossFit; biomechanics; knee stability; exercise protocol